Modeling the relationship between the geometric characteristics of urban green spaces and thermal comfort: The case of Adana city - Cilek, Muge Unal; Uslu, Cengiz (Elsevier, 2022)
In recent years, developing heat stress mitigation strategies in urban areas with the help of climate software has become a top priority in climatic studies to eliminate standardisation deficiency. This paper aimed to statistically determine the climatically suitable and least suitable UGS geometric characteristics in different urban mor-phologies for the hot-humid city of Adana. It combined the climate-based classification of urban morphology with the local climate zone (LCZ), thermal condition analysis of UGS with ENVI-met microclimate software for three different canopy cover scenarios, and statistical analysis results obtained by the one-way ANOVA with post -hoc Tukey-HSD test. Firstly, UGS geometric characteristics (area size, aspect ratio, orientation) and urban morphology were classified. Secondly, mean PET for each UGS and LCZ classes were obtained from ENVI-met. Finally, suitable and least suitable UGS characteristics were determined according to the statistical signifi-cance of PET differences (p > 0.05) using the ANOVA Tukey-HSD test analyzes of pairwise comparisons. The statistical analysis results demonstrated that although the suitable and least suitable UGS characteristics differed in the scenarios, the common characteristics were as follows: The suitable UGS were characterised by larger area sizes, rectangular-shaped, N-S or NW-SE-orientated UGS adjacent to low-rise LCZs (LCZ 3, 6, 7, 8, 10), or small area sizes, all shaped and all orientations UGS adjacent and located to the east of high-rise LCZ classes (LCZ 1 and 4). Shading was an important factor positively affecting thermal conditions. Moreover, the wind circulation and wind speed, which also positively affected thermal comfort, were higher for low-rise buildings than high-rise buildings, open settlements than compact settlements, and 100% grass cover than 100% canopy cover. This study's results can serve as a guide for future researchers and decision makers to standardise UGS characteristics in different urban morphologies and to develop climatically comfortable UGS designs and plan strategies that can be implemented in future cities.
Keywords: ENVI-met; PET; Climatic comfort; Urban green spaces; Geometric characteristics